A Voz de S. Tomé: romper com a modorra vincando o cinzentismo?: (1947-1974) - Nascimento, A. (2015)
The newspaper A Voz de S. Tomé (The Voice of St. Thomas) was created after World War II, more precisely in 1947. Subjected to censorship, written by onlookers, the monolithic A Voz de S. Tomé became the only newspaper where, in addition to pale reflections of local life, was stamped a gray propaganda of political regime and colonial power. The newspaper provided a reading of the world to be adopted by the islanders and the settlers. It will not be too risky to assume that in practice the A Voz de S. Tomé served to perpetuate the isolation of archipelago. This text on the newspaper A Voz de S. Tomé (1947-1974) aims to present contributions to understand the political constraints on the press and characterize its role in the configuration of a public space in a colonized small island, subjected to a dictatorship, that, in 1970, has 73631 inhabitants, which 2391 were white. After the independence in 1975, similar constraints had conditioned the evolution of press in new country, São Tomé and Prince.